Diurnal Wind, Relative Humidity and Temperature Variation in the Stellenbosch-Groot Drakenstein Wine-Growing Area - Bonnardot, V.; Planchon, 0.; Carey, V.; Cautenet, S. (South African Journal of Enology and Viticulture, 2017)
Numerical simulations were performed for 2000-02-03 and 2000-02-04 over the Western Cape in order to observe the alternating sea and land breeze circulation and its effects on diurnal relative humidity and temperature variation, as well as to identify wine-growing areas characterised by high humidity and cool temperature during the maturation period. The Regional Atmospheric Modelling System (RAMS version 4.3) was used at a 1 km resolution. The study domain for the simulation covered a small area from False Bay up to 35 km from the coast. Results are presented using horizontal cross-sections at surface level as well as two south-north cross-sections at longitudes l8°40'E and l8°47'E in order to examine vertical profiles of the atmosphere above the Stellenbosch I Groot Drakenstein winegrowing area. Modelled results agreed with observed data in the vineyards. The sea breeze penetrated at least 35 km inland, but the cooling effect declined rapidly with distance from the sea. Temperature  differences between southern and northern slopes near the sea could be significant enough to be important for viticulture.